(untitled) (World Bulletin of Management and Law, 2022)
The problem of the study was the absence of a knowledge product about the impact of spreading the green quality function in Iraqi companies or others, especially in the field of electrical and electronic industries, and this indicates the existence of a knowledge gap. The current study aims to test the possibility of applying the deployment of the green quality function in the company under study, as an attempt to fill the knowledge gap in explaining the nature of the relationship through a survey of the opinions of a group of individuals working in the company under study. To achieve this goal, the current study concluded that the deployment of the green quality function works to transform the needs of customers into engineering standards for design and production and successfully integrate the ideas of green energy and green environment in the process of producing the green product according to customer